مشكلات تعليم اللغة العربية - Rahmati, Suci; Muslim, Buhori; Mubshirah, Dara (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Arabic language learning purposes to encourage, guide, develop, and enhance Arabic languages.Skills included listening, speaking, reading and writing. In the fact, the Arabic language learning has some problems. The aim of this study is to analyze various problems in learning of Arabic language. The method used in this study is descriptive methode, which is a study that collects data in the form of words and picture without number. The results of this study indicate that two big problems in learning Arabic language, there are linguistic problems and non linguistic problems. The linguistic problems included sound, vocabularies, structure and writing. Non-linguistic problems included teachers, motivaties, fasilities, socio cultural, textbooks, characteristics, methods and times.